Calculus: Early Transcendentals (2nd Edition)

Published by Pearson
ISBN 10: 0321947347
ISBN 13: 978-0-32194-734-5

Chapter 3 - Derivatives - 3.4 The Product and Quotient Rules - 3.4 Exercises: 12

Answer

$f'(x) = 2x-\frac{2}{x^3}$

Work Step by Step

$f(x) = (1+\frac{1}{x^2})(x^2+1) = x^2+1+1+\frac{1}{x^2} = x^2+2+x^{-2}$ $f'(x) = 2x-2x^{-3} = 2x-\frac{2}{x^3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.